1998
DOI: 10.1105/tpc.10.5.753
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell-Specific Inositol Metabolism and Transport in Plant Salinity Tolerance

Abstract: myo-Inositol and its derivatives are commonly studied with respect to cell signaling and membrane biogenesis, but they also participate in responses to salinity in animals and plants. In this study, we focused on L -myo -inositol 1-phosphate synthase (INPS), which commits carbon to de novo synthesis, and myo -inositol O -methyltransferase (IMT), which uses myo -inositol for stress-induced accumulation of a methylinositol, D -ononitol. The Imt and Inps promoters are transcriptionally controlled. We determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(82 citation statements)
references
References 47 publications
(52 reference statements)
7
74
0
1
Order By: Relevance
“…Osmoprotective functions of free myo-inositol have been demonstrated in plants (Sheveleva et al 1997;Nelson et al 1998;Klages et al 1999), with conclusive evidence recently demonstrated in transgenic tobacco (Majee et al 2004).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Osmoprotective functions of free myo-inositol have been demonstrated in plants (Sheveleva et al 1997;Nelson et al 1998;Klages et al 1999), with conclusive evidence recently demonstrated in transgenic tobacco (Majee et al 2004).…”
Section: Introductionmentioning
confidence: 83%
“…is the precursor to its methyl ethers that in turn, have been shown to accumulate in response to environmental stress as compatible solutes (Bohnert et al 1995;Ishitani et al 1996;Nelson et al 1998). Osmoprotective functions of free myo-inositol have been demonstrated in plants (Sheveleva et al 1997;Nelson et al 1998;Klages et al 1999), with conclusive evidence recently demonstrated in transgenic tobacco (Majee et al 2004).…”
Section: Introductionmentioning
confidence: 98%
“…In M. crystallinum , the de novo synthesis of inositol (as a precursor to ononitol and pinitol) proceeds from glucose 6-phosphate through two steps catalysed by myo-inositol-1-phosphate synthase (INPS) and inositol monophosphatase (IMP; Nelson et al , 1998). Wild-type and mutant M. crystallinum accumulated similar amounts of cyclitols under salinity, indicating that starch mobilization is not required for the synthesis of these compatible solutes, which are thus likely to be derived from primary photosynthate and/or processing of the soluble sugar pool.…”
Section: Discussionmentioning
confidence: 99%
“…The His-tagged protein was purified with Ni-NTA Agarose (Qiagen) under denaturing conditions. The purified protein (43 Kda) was used to raise polyclonal antibodies against the IMT enzyme [50], which were subsequently used in Western analyses of transgenic lines.…”
Section: Methodsmentioning
confidence: 99%